2018
DOI: 10.1177/1357633x18811757
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of telemonitoring versus usual care for chronic obstructive pulmonary disease: A systematic review and meta-analysis

Abstract: Aims The purpose of this research was to investigate the effectiveness of telemonitoring for chronic obstructive pulmonary disease. Methods We searched MEDLINE, EMBASE, the Cochrane Central Register of Controlled Trials and CINAHL up to September 2018. We selected randomised controlled trials comparing telemonitoring and control groups for chronic obstructive pulmonary disease management. Two reviewers independently examined articles based on eligibility, extracted data and evaluated the risk of bias. The Coch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
48
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 50 publications
(56 citation statements)
references
References 43 publications
4
48
0
Order By: Relevance
“…e list of excluded literature studies and reasons of exclusion are displayed in Appendix 2 in Supplementary materials. us, a total of 8 SRs and MAs [16][17][18][19][20][21][22][23] were finally included in this overview. e study selection process is shown in Figure 1.…”
Section: Study Identificationmentioning
confidence: 99%
See 4 more Smart Citations
“…e list of excluded literature studies and reasons of exclusion are displayed in Appendix 2 in Supplementary materials. us, a total of 8 SRs and MAs [16][17][18][19][20][21][22][23] were finally included in this overview. e study selection process is shown in Figure 1.…”
Section: Study Identificationmentioning
confidence: 99%
“…We included six systematic review and meta-analysis [16-18, 20, 22, 23], one meta-analysis [19], and one systematic review, which were published between 2011 and 2019, with four from Asian countries [16][17][18][19] and four from European countries [20][21][22][23], and all databases reviews retrieved ranged from one to six, with PubMed, Embase, and Cochrane Library as the most widely searched databases. e number of RCTs included in each review ranged from 3 to 28, and the total participants ranged from 391 to 3645.…”
Section: Characteristics Of Included Reviewmentioning
confidence: 99%
See 3 more Smart Citations